(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Significant advancements in the past few years have resulted in improved Smart Building technologies for connectivity and protection. This article provides an overview of these developments. In addition, we provided a patient nurture scheme for clinic buildings as well as a layered Building Management System (BMS) architecture in this article. Then we conducted a comparison of our system to other comparable systems and highlighted the advantages of our method. Furthermore, we suggested several security measures based on the design and further study. In addition, this article includes a comparison of our system to other comparable systems. The advantages of our enterprise are then enumerated and discussed. Finally, we researched and utilized the Contiki OS and the Cooja emulator, as well as creating simulations, to get a more comprehensive and truthful picture of our system. The consequences of the data packet transfer are important since the protocol we employ has a very low proportion of packets lost, if not none at all With the Cooja simulator, we watch data in and into of the networks in real time. As a result, it seems to be a very helpful tool that provides, in addition to traffic, diagrams and other data that characterize our system. We want to mimic our whole system in the future using technologies like the Cooja emulator. We will then proceed with the installation of such a system if the outcomes are as anticipated. This article will serve as a starting point for making better choices in the future when developing smart structure systems.